Heat and Mass Transfer in Porous Media - Delgado, J.M.P.Q.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book, "Heat and Mass Transfer in Porous Media", presents a set of new developments in the field of basic and applied research work on the physical and chemical aspects of heat and mass transfer phenomena in a porous medium domain, as well as related material properties and their measurements. The book contents include both theoretical and experimental developments, providing a self-contained major reference that is appealing to both the scientists and the engineers. At the same time, these topics will encounter of a variety of scientific and engineering disciplines, such as chemical, civil, agricultural, mechanical engineering, etc. The book is divided in several chapters that intend to be a short monograph in which the authors summarize the current state of knowledge for benefit of professionals.
Treatment of Rising Damp in Historical Buildings -- The Evaluation of Hygroscopic Inertia and Its Importance to the Hygrothermal Performance of Buildings -- Two-phase flow and heat transfer in micro-channels and their applications in micro-system cooling -- Numerical Methods for Flow in Fractured Porous Media -- Lungs as a Natural Porous Media: Architecture, Airflow Characteristics and Transport of Suspended Particles -- On Analogy between Convective Heat and Mass Transfer Processes in a Porous Medium and a Hele-Shaw Cell -- Heat and Mass Transfer in Porous Materials with Complex Geometry: Fundamentals and Applications -- Contribution to Thermal Properties of Multi-Component Porous Ceramic Materials used in High-Temperature Processes in the Foundry Industry -- Metal Foams Design for Heat Exchangers: Structure and Effectives Transport Properties -- Heat and Mass Transfer in Matrices of Hygroscopic Wheels.
Keywords: Engineering; Surfaces (Physics).; Materials Science; Characterization and Evaluation of Materials; Engineering Thermodynamics, Heat and Mass Transfer